Perancangan Prototype Sistem Pendeteksi Kebocoran Gas dengan Menggunakan Sensor MQ-9 Berbasis Arduino Uno - Putra, Aden Rahman; Arfaez, Ezra; Abellani, Farica; Sunanto, Hari; Gumay, Andesvan (Syntax Literate, 2026)
LPG gas leaks are a serious threat that can trigger fires and endanger human safety. To overcome this problem, this study designed a prototype gas leak detection system based on the Arduino Uno microcontroller using the MQ-9 sensor. This sensor has high sensitivity to LPG, carbon monoxide, and methane. The system is designed to detect gas leaks automatically and in real-time, and provide early warnings through a buzzer sound, a gas level display on a 16x2 LCD, and an exhaust fan activation to reduce gas concentrations in the air. This study uses an Engineering Research approach and goes through the stages of needs analysis, design, implementation, and system testing. The test results show that the system is able to respond quickly and effectively to the presence of hazardous gases, thus potentially improving safety and preventing accidents due to gas leaks in closed environments.